KESETARAAN GENDER DALAM PANDANGAN ISLAM - Agustina Damanik (Jurnal AL-MAQASID: Jurnal Ilmu Kesyariahan dan Keperdataan, 2018)
In the view of Islamic law, everything is created by God by nature. Similarly human beings, between men and women as individuals and sex have their own nature. The Qur'an recognizes anatomical differences between men and women. the nature of women is often used as an excuse to reduce the various roles of women in the family and society, men are often perceived to be more dominant in playing roles, while women have a limited role in the domestic sector. Culture that develops in society also views that women as weak creatures, emotional, smooth and shy while men are strong, rational, rough and brave creatures. Strangely these differences are then believed to be natures, which are still the gifts of God. Whoever tries to change it is considered to violate nature and even oppose God's decree. The role and status of women in Islamic perspectives has always been attributed to the presence of men. Women are described as being whose existence depends heavily on men. As a child, he is under the guardianship of his father and brother, as the wife depends on the husband. Islam establishes women as husbands as husbands, as mothers who nurture and educate children and keep property and foster family ethics in the smallest government.